Configuration Design for 6-DOF Master Manipulator and Research on Spatial Trajectory Planning Simulation - Qingyun Wang; Lü Ning; Zhidong Liu; Junying Zhao; Wenshuang Chang (Jixie chuandong)
The master manipulator is an important part for minimally invasive surgical （MIS）robot. It is used to receive the doctor action and control the slave operator to complete the surgical operation. Based on analysis of the application requirements of the master manipulator that is already existed，the configuration design requirements of the master manipulator are analyzed，and the configuration design of the master manipulator is completed. The trajectory planning simulation of the master manipulator in joint space is also carried out，and the displacement，velocity and acceleration curves of the master manipulator joint are obtained. The simulation results show that，the configuration design of the master manipulator is reasonable，and the master manipulator moves smoothly，which lays a theoretical foundation of the further design and optimization for the master manipulator.